Three dimensional AlN skeleton-reinforced highly oriented graphite flake composites with excellent mechanical and thermophysical properties. (May 2018) - Zhang, Xiaoyu; Shi, Zhongqi; Zhang, Xia; Wang, Ke; Zhao, Yingying; Xia, Hongyan; Wang, Jiping
Abstract: To obtain light, strong materials with high thermal conductivity and low coefficient of thermal expansion (CTE), three-dimensional (3D) AlN ceramic skeleton reinforced highly oriented graphite flake (AlN/GF) composites were successfully prepared by combining vacuum filtration and spark plasma sintering. The effects of AlN content on the microstructure, mechanical and thermophysical properties of the composites were investigated. It was found that the introduction of AlN together with Y2 O3 significantly promoted the densification and mechanical properties of the composites. The GF grains in the composites were highly oriented with the Lotgering factor >98%, and a 3D continuous ceramic skeleton was formed when the AlN content increased to 20 wt%. The formed ceramic skeleton tailors the thermophysical properties of the composites effectively. Particularly, the unfavourable high through-plane CTE (∼28 × 10 −6  K −1 ) of highly oriented graphite matrix remarkably decreased to a low value (∼7 × 10 −6  K −1 ) due to the thermal expansion constraint of the formed ceramic skeleton architecture. The 20 wt% AlN/GF composite possessed the best comprehensive properties with the bending strength >80 MPa, high in-plane thermal conductivity of 442 W m −1  K −1 and low through-plane CTE value of 7.3 × 10 −6  K −1 . Our strategy would facilitate the practical application of graphite-based composites in current demanding thermal management. Graphical abstract: Image 1